Radiation Effect on the Optical& Structural Properties of CdTe: Zn thin Films - Issa, Suad I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The Films of CdTe:Zn were prepared on a glass by using vacuum vapor deposition technique .The x-ray diffraction pattern revealed that the films have polycrystalline with FCC structure and the preferred orientation was along (111) plane.  The films were exposed to a low dose of gamma ray.(5ÂµCi for 30 days) Transmission and absorptance spectra were recorded in the range of (400-1100) nm before and after irradiation. It was found that irradiation has a clear effect on the optical and structural properties which include the transmition and absorption spectra, extinction coefficient, refractive index, and the energy gap.